Asian Insolvency Regimes from a Comparative Perspective: Problems and Issues for Reform - Nam, Il Chong; Oh, Soogeun (Insolvency Systems in Asia: An Efficiency Perspective, 2001)
The 1997-1998 Asian financial crisis exposed serious deficiencies in the insolvency systems of many countries. In response, many governments have undertaken sweeping reforms to strengthen their insolvency systems and rebuild their economies, including promulgating new laws, introducing new procedures to facilitate restructuring, strengthening courts and related institutions, and recapitalising financial institutions. This volume brings together a comparative report and studies of the insolvency systems of Indonesia, Korea, Malaysia, the Philippines, Singapore and Thailand. These papers examine, among other things, the extent to which each country was affected by the financial crisis, the effectiveness and efficiency of formal and informal insolvency procedures, recent initiatives undertaken, and areas in need of further reforms. In addition, this publication includes an introductory note summarising the findings and conclusions from the November 1999 conference on "Insolvency Systems in Asia: An Efficiency Perspective.